Association Between Body Mass Index and Functional Outcomes in Elderly Patients with Extra-Articular Distal Radius Fracture: A Prospective Observational Study - Rios-Riquelme, M (Springer, 2021)
Introduction: The association between body mass index (BMI) and functional outcomes is unknown in elderly individuals with distal radius fracture (DRF). Objective: The aim of this study is to evaluate if there is association between BMI and functional outcomes in patients older than 60 years with DRF treated conservatively. Materials and Methods: A prospective observational study was performed. A total of 228 patients with extra-articular DRF were prospectively recruited. All patients were categorized by their BMI as normal, overweight, or obese. Functional outcomes were assessed after cast removal and at 1-year follow-up. The Disabilities of the Arm, Shoulder and Hand Outcome Measure (DASH), and Patient-Rated Wrist Evaluation (PRWE) questionnaires were used to assess upper limb and wrist/hand function, respectively, while the Jamar Dynamometer was used to assess grip strength. Results: Of the total number of patients, 184 were female (80.7%), 87 were overweight (38.2%), and 111 were obese (48.7%). After cast removal, the correlations between BMI and functional outcomes were DASH 0.06 (p = 0.578), PRWE 0.04 (p = 0.692), and grip strength − 0.02 (p = 0.763). At 1-year follow-up, the correlations were DASH 0.55 (p = 0.036), PRWE 0.32 (p = 0.041), and grip strength − 0.21 (p = 0.043). Conclusion: This study suggests that at 1-year follow-up, there was a low-to-moderate association between BMI and poor functional outcomes in elderly patients with extra-articular DRF treated conservatively. Level of Evidence: Level IV, observational prospective study. © 2021, Indian Orthopaedics Association.